Plasma energy and work function of conducting transition metal nitrides for electronic applications - Matenoglou, G. M.; Patsalas, Panos; Koutsokeras, Loukas E. (My University, 2009)
The combination of electrical conductivity, chemical and metallurgical stability, refractory character, having lattice constants that are close to those of III-nitrides makes transition metal nitrides promising candidates for electronics and device applications. We study the structure, stability, and the plasma energy of stoichiometric, transition metal nitrides of similar crystal quality as well as the widest variety of their ternaries ever reported. We establish the phase spaces of the plasma energy (6.9-10.5 eV) and the work function (3.7-5.1 eV) of these complex nitrides with their lattice constant (0.416-0.469 nm) and we investigate the limits of their applications
Keywords: Physics; Nitrides; Plasma stability; Electric conductivity